Impact of Stripe Rust on Yield Loss of Wheat and Its Status In Haryana, India - Singh, Rajender (Bangladesh Journal of Botany, 2022)
Stripe rust caused by Puccinia striiformis f. sp. tritici (Pst) is a major constraint in all wheat-growing countries. Surveys conducted during 2015-19 in Haryana, maximum stripe rust severity recorded in Yamuna Nagar (28.57%) followed by Ambala (23.33%) and least observed in Fatehabad (5%).Two commonly prevalent pathotypes 46S119 and 110S119 were in all 4 crop seasons followed by 238S119 occurrence in two seasons. Infection range was 0-80S in varieties HD2967, Shri Ram152, Shri Ram171, Shri Ram3132, Barbett, WH147 and HD2851. Maximum terminal disease severity contracted by WH 147 (100%), HD2967 (100%) and PBW 343(96.66 %) in seedling stage disease appearance followed by tillering stage and least disease severity was observed on milk development. Stripe rust symptoms produced 14 days after artificial inoculation with urediniospores (106/ml) of Puccinia striiformis f. sp. tritici. Maximum avoidable yield loss was obtained in WH 147 (73.14%) followed by HD2967 (68.35%), PBW343 (60.08%) and least recorded in WH1105 (20.26%) on seedling stage. Minimum yield loss in varieties was recorded at milk development stage. There was significant correlation (0.90) between disease severity and avoidable yield loss with the coefficient of determinant, R2= 0.80. Bangladesh J. Bot. 51(4): 647-653, 2022 (December)